Lipoarabinomananos de micobacterias : efectos sobre la respuesta inmune en bovinos - Colavecchia, Silvia (2011)
Vaccination is the most effective method to control an infection. Effective vaccines induce a protective immune response by activating T and B lymphocytes, which, converted into memory cells, control infections caused by the pathogens included in the vaccine formulation. Vaccines made from inactivated viruses or bacteria or subunits have the ability to generate an efficient specific immune response. However, this response is sometimes weak because the viruses or bacteria do not multiply inside the host. Because of this, the use of adjuvants is required to enhance the immune response. The selection of an appropriate adjuvant can not only enhance the immune response, but also modulate the immunoglobulin isotype and the type of profile (Th1 or Th2) produced. Lipoarabinomannan (LAM) is non-covalently bound to the plasma membrane of mycobacteria and extends to the outer part of the cell wall. This molecule plays an important role in the physiology of bacteria as well as in the modulation of the host immune response during infection. Several groups of researchers have described the effects of mycobacteria as adjuvants and modulators inducing a Th1 response when added to vaccines. The aim of this thesis was to evaluate the effect of the application of ovalbumin (OVA) together with LAM and incomplete Freund's adjuvant (IFA) on the specific cellular and humoral immune response of bovines to OVA. LAM was extracted and purified from Mycobacterium avium subsp. avium using a chemical extraction, as previously (Hamasur et al., 1999). The yield obtained was similar to that obtained by those authors. Using the monoclonal antibody that specifically recognizes LAM of Mycobacterium tuberculosis, we confirmed that the structure of LAM obtained from cultures of Mycobacterium avium subsp. avium retains a high degree of antigenic\nsimilarity to that of Mycobacterium tuberculosis.\nA total of 22 crossbred calves between 10 and 12 months of age were\nused. Calves were randomly assigned to four treatment groups: G-IFA,\nimmunized with PBS and 1 mL of IFA; G-LAM, immunized with LAM (1\nmg/dose) and IFA; G-OVA, immunized with OVA (1 mg/dose) and IFA; and\nG-OVALAM, immunized with OVA, IFA and LAM. Animals were immunized\nsubcutaneously on days 0, 21 and 42. Since one of the most important limiting factors for the use of adjuvants is the possible direct or indirect toxic\neffect on products derived from human consumption, a number of physiological parameters were evaluated to control the formulation of the immunogen used.\nThe analysis of the these parameters (hematological values, complete\nblood count, serum protein profile, weight gain, and reactivity to purified\nprotein derivative of Mycobacterium avium subsp. avium (PPA)) indicated that the treatment with LAM did not induce detectable alterations. This could be a first approach for the assessment of the safety of the immunomodulator. We then evaluated the innate immune response by\ndetecting the production of reactive oxygen intermediates in adherent\nperipheral cells at time 0 (pre-immunization) and final time (15 days postthird\nimmunization) and detected a decrease in the production of the reactive oxygen intermediates in the G-OVALAM group at the final time. The modulation produced in the cellular immune response was\nassessed by the proliferation of mononuclear cells stimulated with mitogens\nand antigens, lymphocyte subpopulations in peripheral blood, IFN production at time 0 and final time, and specific skin hypersensitivity. A significant increase was detected in the proliferative response of the animals belonging to the group G-OVALAM, indicating that LAM increases the specific\ncellular immune response with mitogens such as ConA. An increase in IFN? production was observed in culture supernatants of\nmononuclear cells stimulated in vitro with OVA and ConA, in animals treated\nwith LAM at levels of between 600 and 800 pg/mL. An increase in the\npercentage of cells with the CD25 marker on the surface was also observed.\nThe expression of this marker is associated with the increase in\nsubpopulations with regulatory functions, although these functions have not been demonstrated in cattle. Since the specific response against purified\nprotein derivative of Mycobacterium bovis could not be detected in groups\ninoculated with LAM as an immunomodulator, the results indicate that\nmodulation by LAM does not interfere with the diagnosis of tuberculosis in\nvivo or with that of paratuberculosis in vitro.\nThe kinetics of the specific antibody response against OVA was evaluated on days 0, 21, 42 and 57, whereas the response of isotypes was analyzed using bovine IgM, IgG1, IgG2 and IgG3 antibodies. The results\nshow that the modulation by LAM in cattle induced specific high titers of\nantibodies as from the first immunization. These levels increased with the\nsecond dose and remained at the same level after the third immunization.\nThe serum response against OVA was predominantly IgG1 and IgG2, and\nIgG3 to a lesser extent. The IgG1/IgG2 relationship showed a decrease in\nthe animals immunized with LAM. This suggests a trend of LAM to induce a\nTh1 response. This thesis allowed determining the effect of the addition of LAM to the incomplete Freund's adjuvant as a potential modulator to a Th1 response\nagainst OVA when it is simultaneously inoculated.